Long-Term Clinical Outcomes After Percutaneous Coronary Intervention With Drug-Coated Balloon-Only Strategy in de novo Lesions of Large Coronary Arteries - Hu, Feng-Wang; Chang, Shang; Li, Qian; Zhu, Yong-Xiang; Wang, Xin-Yu; Cheng, You-Wei; Zhou, Qi-Hua; Liu, Bing; Iqbal, Javaid; Tang, Xiao-Xia; Zhang, Yao-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background and Objectives: Use of drug coated balloon (DCB)-only strategy for revascularization of native large coronary artery lesions is on the rise. The long-term efficacy of this approach for bifurcation and non-bifurcation lesions remains unknown. We aim to assess the long-term clinical outcomes of DCB-only strategy for the treatment of de novo bifurcation and non-bifurcation lesions in large coronary arteries. Methods: This multicenter, prospective, observational study, enrolled 119 patients with de novo coronary lesions in vessels ≥2.75 mm. The primary endpoint was the rate of clinically driven target lesion failure (TLF), a composite of cardiac death, target vessel myocardial infarction, and clinically driven target lesion revascularization (TLR). Patients were followed up for a median of 2 years. Results: Of 119 patients with 138 lesions, 66 patients (75 lesions) had bifurcation and 53 patients (63 lesions) had non-bifurcation lesions. Average reference vessel diameter of 3.1±0.3 mm and there was no difference in bifurcation and non-bifurcation group (3.0±0.3 vs. 3.1±0.3mm; p=0.27). At 2-year follow-up, the TLF occurred in 5 (4.2%), TLR in 4 (3.4%) and target vessel revascularization (TVR) in 5 (4.2%) cases. The frequency of TLR and TVR was higher in non-bifurcation group (p=0.04 and p=0.02, respectively), but there were no differences in TLF between two groups (p=0.17). The cumulative incidence of TLF (Kaplan-Meier estimates) was also not different in the two groups (Log Rank p=0.11). Conclusions: DCB-only strategy for de novo lesions in large coronary arteries appears to be safe and effective for both bifurcation and non-bifurcation lesions. Further randomized clinical trials are warranted to confirm the value of DCB-only strategy in de novo bifurcation lesions of large vessels.